ADVERTISING PAY PER CLICK (PPC) DENGAN GOOGLE ADSENSE PERSPEKTIF HUKUM ISLAM - Dika Saputri (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
The internet as an effective medium in the world of business (especially in the field of marketing) from the viewpoint of the bisins tomarket the products produced. Various models of product offerings areconceptualized by business people issued to capture market segments.Pay per Click (PPC) is one of several programs on the internet that hasthe concept of giving gifts to internet users when openingadvertisements submitted by advertising companies through certainsites. One dollar producer from the internet is Google Adsense. GoogleAdsense is a dollar-producing affiliate program issued by GoogleSearch Engine companies by collaborating with web or blog owners interms of Advertising. With this kind of affiliate business model,publishers (web owners or blogs) will get dollars from advertisementsdisplayed on the web or blog. Ads displayed on the web or blog can betext or images. There are many titles for revenue generated fromGoogle Adsense. And to find out whether or not the Muslim communityis capable of following a business in the field of Advertising, such asPay Per Click (PPC), there needs to be a study that discusses thebusiness of Islamic Law.